2012
DOI: 10.1371/journal.pone.0030100
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Whole Transcriptome Sequencing in Castor, Directed at Understanding Triacylglycerol Lipid Biosynthetic Pathways

Abstract: BackgroundStorage triacylglycerols in castor bean seeds are enriched in the hydroxylated fatty acid ricinoleate. Extensive tissue-specific RNA-Seq transcriptome and lipid analysis will help identify components important for its biosynthesis.Methodology/FindingsStorage triacylglycerols (TAGs) in the endosperm of developing castor (Ricinus communis) seeds are highly enriched in ricinoleic acid (18:1-OH). We have analysed neutral lipid fractions from other castor tissues using TLC, GLC and mass spectrometry. Coty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 71 publications
8
98
0
Order By: Relevance
“…The proportion of oleoyl-CoA was similar in all lines (Fig. 3A), and HFA-CoA accumulated to less than 10% in CL37, similar to levels of HFA in developing castor seeds (39). Additionally, the acyl-ACP compositions of all four lines were very similar (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…The proportion of oleoyl-CoA was similar in all lines (Fig. 3A), and HFA-CoA accumulated to less than 10% in CL37, similar to levels of HFA in developing castor seeds (39). Additionally, the acyl-ACP compositions of all four lines were very similar (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…18:2/3-PC, 18:1OH-PC over 18:1-PC; 18:1-DAG over 18:2/3-DAG, 18:1OH-DAG), since the desaturases and the hydroxylase will enrich the PC pool with the PUFAs and hydroxylated FAs. On the other hand, although the RcROD1 protein has been detected in castor endosperm (Brown et al, 2012), previous results suggested that the castor PDCT unlikely preferred HFA-containing substrates, since microsomal preparations from castor endosperm rapidly turned the glycerol-labeled diricinoleoyl-DAG to TAG, whereas dioleoyl-DAG was preferentially used in PC synthesis (Bafor et al, 1991). Moreover, Dahlqvist et al (2000) showed that castor bean microsomes preferentially metabolized ricinoleoyl-PC to TAG (probably via PDAT), whereas oleoyl-PC was preferentially metabolized to DAG (probably via PDCT).…”
Section: Discussionmentioning
confidence: 95%
“…2, A-C) (40,41). RcSUS1 belongs to the dicot SUS1 group and has high sequence identity with soybean root nodule (GmSUS1) and Arabidopsis anoxiainducible (AtSUS1 and AtSUS4) orthologs (Table 2) (5, 21).…”
Section: Discussionmentioning
confidence: 99%
“…C, cotyledon; dE and dC, endosperm and cotyledon, respectively, from stage V developing COS that had been depodded for 48 h; D, dry (mature) COS; G, germinating COS endosperm harvested at 5 days postimbibition. pair of transcriptome sequencing studies (40,41). Both reports clearly established RcSUS1 as the dominant SUS isozyme expressed in the endosperm of developing COS and that its expression is maximal during the early stages of COS development (Fig.…”
Section: Rcsus1 Is the Dominant Sus Isozyme Expressed In Develop-mentioning
confidence: 94%